Internal Net Worth and the Investment Process: An Application to U.S. Agriculture - Hubbard, R. Glenn; Kashyap, Anil K. (Journal of Political Economy, 1992)
Recent models of firm investment decisions stressing informational imperfections in capital markets provide a foundation for interpreting evidence that movements in internal finance can predict investment spending, even after one controls for measures of firms' investment opportunities. While such evidence is suggestive, it is often open to other interpretations. We examine these models using data on equipment investment in the U.S. agricultural sector. This sector is particularly interesting because it has experienced large fluctuations in net worth and the profitability of investment, and reasonable measures of net worth can be constructed. Our findings provide support for a class of "internal funds" models of investment under asymmetric information.